The gall midges (Diptera: Cecidomyiidae) of Apiaceae in Israel - Dorchin, Netta; Freidberg, Amnon (Zootaxa, 2011)
The Israeli fauna of gall midges (Diptera: Cecidomyiidae) associated with plants of the family Apiaceae consists of three species of Lasioptera and two species of Schizomyia that all appear to be monophagous and univoltine. Lasioptera foeniculi n. sp. and Schizomyia botellus n. sp. are described as new to science. Lasioptera carophila, Lasioptera umbelliferarum and Schizomyia buboniae are redescribed, and a neotype is designated for L. umbelliferarum. The genera Paraschizomyia Möhn and Microlasioptera Skuhravá and Skuhravý are synonymized under Schizomyia Kieffer and Lasioptera Meigen, respectively. The two Israeli Schizomyia species develop in complex bud galls on the desert plants Deverra tortuosa and Deverra triradiata and are the only known Schizomyia species that pupate inside their galls. The three Lasioptera species develop in stem or fruit galls on Foeniculum vulgare and Bilacunaria boissieri in the Mediterranean region of Israel. Larvae, pupae and adults of these gall midges are described and information is provided about their biology, distribution and taxonomic relations.